Processing, utilization and challenges of African locust bean (Parkia biglobosa, Jacque Benth) in Arigidi Akoko, Ondo State, Nigeria (2013)
The study examined the processing, utilization and challenges of African locust bean (Parkia biglobosa) in Arigidi Akoko in Akoko Northwest Local Government Area of Ondo State. A total of 3,446 locust beans sellers were identified and 5% of the sellers were sampled given the total of 172 respondents: 80 at Imo Arigidi Oja, and 42 at Agbaluku which are the three major settlements in the town. Data were collected using a structured questionnaire and subjected to descriptive statistical tools. The socio-economic analysis shows that locust beans processing and trade are dominated by females (97.7%) with trace percentage of male (2.3%). This could be traced to preference of women in processing operations. The prevalent method of processing is manual or traditional. Majority of the respondents (48.8%) believed the processing method is strenuous and it takes a lot of time. However, 32% of the people considered it simple and less stressful but 2.3% perceived the activities to be simple, stressful and time-consuming. Similarly, 59.9% of respondents only submitted that the processing method could be learnt while 57.6% of the respondents specified the number of days in which the processing method could be learnt (1-7 days). The processing/utilization challenges include unavailability of the product in large proportion in the study area, lack of water supply, stressful nature of processing, poor packaging, lack of storage facilities, etc. based on the results of the study it can be concluded that locust bean processing is a thriving occupation and therefore a sustainable livelihoods for the people of Arigidi Akoko. For promotion of occupation or the locust bean trade in the area, modernized processing techniques, provision of boreholes by relevant government agencies to ensure potable water supply for processing activities and encouragement of plantation establishment should be considered.